The Emerald handbook of computer-mediated communication and social media - Lipschultz, Jeremy Harris, 1958-; Freberg, Karen June; Luttrell, Regina, 1975- (Emerald Publishing Limited, 2022)
Uniquely relating social media communication research to its computer-mediated communication foundation, as well as digital and emerging media trends, this handbook is an indispensable resource whether you're a graduate student or a seasoned practitioner.- Resumé vydavatel
Keywords: sociální média; internetové sociální sítě; internetová komunikace; social media; Internet social networks; Internet communication; elektronické knihy; příručky; electronic books; handbooks and manuals